The Effect of Work Experience and Work Discipline on Employee Performance at PT. BCA Tbk Pamulang Branch - Prasetyo Kurniawan (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2022)
This study aims to determine the Effect of Work Experience and Work Discipline on Employee Performance at PT BCA Tbk Pamulang Branch. The research methodology used uses the quantitative method. The population in this study was all employees who worked at PT BCA Tbk Pamulang Branch as many as 51 people. The sample used was 51 respondents using saturated sampling techniques. The data analysis method uses a simple linear regression test, multiple linear regression, correlation coefficient, coefficient of determination, partial t-test and simultaneous F test. The results showed that: (1) There was a positive and significant influence between work experience on employee performance at PT BCA Tbk Pamulang Branch, this can be proven from the tcount of 7.692 > ttable 2.009 with a significant level of 0.000 <0.05. (2) There is a positive and significant influence between work discipline on employee performance at PT BCA Tbk Pamulang Branch, this can be proven from the tcount of 6.126 > ttable 2.009 with a significant level of 0.000 <0.05. (3) Simultaneously there is a positive and significant influence between work experience and work discipline on employee performance at PT BCA Tbk Pamulang Branch, this can be proven from the value of Fcount 36.760 > Ftable 4.04 with a significant level of 0.000 <0.05.